Relasi Ekospiritualisme Tradisi Ruwat Rambut Gimbal di Dieng - Melati, Freska Ela; Sukmawan, Sony (ppjbsip, 2025)
This study aims to examine in depth the practice of ruwat rambut gimbal (hair cutting ritual) as a form of dialectical and equal relationship between material, spiritual, and ecological entities. This study uses a descriptive qualitative method with a field design related to oral and written texts of the ruwat rambut gimbal tradition. Data were collected through observation, interviews, and documentation studies. The data analysis technique uses the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing with a hermeneutic approach to understand the symbolic meaning of texts and cultural actions. The results show that in the tradition of ruwat rambut gimbal, with a post-humanism and new animism approach, there are three harmonious relationships. The first relationship is material, involving dreadlocks, offerings, and children's requests. The second relationship is spiritual, involving belief in ancestral spirits and the use of Javanese songs and Islamic prayers as a medium of communication. The third relationship is ecological, involving the preservation of water sources, land, the sacred area of Dieng, and the management of agricultural products. These three relationships are interrelated in presenting the practice of gimbal hair, which shows the existence of a communication network between humans and non-human entities. The implications of this research enrich the understanding of cultural sustainability while strengthening ecological and spiritual awareness to maintain harmony between humans, nature, and ancestors, especially in the Dieng Plateau. AbstrakPenelitian ini bertujuan mengkaji secara mendalam praktik ruwat rambut gimbal sebagai wujud relasi dialektik dan setara antara entitas material, spiritual, dan ekologis. Penelitian ini menggunakan metode kualitatif deskriptif dengan desain lapangan yang berkaitan teks-teks lisan dan tertulis tradisi ruwat rambut gimbal. Data dikumpulkan melalui observasi, wawancara, dan studi dokumentasi. Teknik analisis data menggunakan model Miles dan Huberman yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan dengan pendekatan hermeneutik untuk memahami makna simbolik dari teks maupun tindakan budaya. Hasil penelitian menunjukkan bahwa tradisi ruwat rambut gimbal pendekatan posthumanisme dan animisme baru, memiliki tiga relasi yang saling terhubung. Relasi pertama berupa material rambut gimbal, sesaji, dan benda permintaan anak. Relasi kedua berupa spiritual terhadap kepercayaan roh leluhur maupun penggunaan tembang Jawa dan doa Islam sebagai media komunikasi. Relasi ketiga berupa ekologis dalam menjaga sumber air, tanah, kawasan suci Dieng, serta pengelolaan hasil bumi. Ketiga relasi tersebut saling menguatkan dan mempresentasikan jaringan komunikasi antara manusia dengan entitas nonmanusia. Implikasi penelitian ini memperkaya pemahaman keberlanjutan budaya sekaligus memperkuat kesadaran ekologis dan spiritual untuk menjaga harmoni antara manusia, alam, maupun leluhur khususnya di Dataran Tinggi Dieng.